Complete Disappearance of Lung Abnormalities on High-Resolution Computed Tomography: A Case of Histiocytosis X - Sergio Negrin-Dastis; Dominique Butenda; Jacques Dorzee; Jacques Fastrez; Jean-Paul d’Odémont (Canadian Respiratory Journal)
A case of pulmonary Langerhans cell histiocytosis, proved by both lung high-resolution computed tomography and lung biopsy, is described. Following smoking cessation, lung nodules and cysts gradually disappeared on serial computed tomography scans, with complete clearance of the lesions after 12 months. The role of tobacco smoking is discussed, in detail, against the background of the literature.